Morbi-mortalidade neonatal decorrentes de síndromes hipertensivas - SOUSA, Diogo Barros Florenzano de (2023)
Objectives: Evaluate neonatal morbidity and mortality resulting from hypertensive disorders of pregnancy admitted to the Santa Casa de Misericórdia do Pará, for the purpose of obstetric care. Methods: Longitudinal prospective study description of the institutional basis of 148 pregnant women with hypertension, in which we assessed the variables prenatal care, birth preterm, birth weight, gestational age, Apgar score at 1 and 5 minutes, parity, hypertension in previous births signs of fetal distress, destination after the birth, evolution of the newborn, maternal blood pressure level and the presence of asymmetric fetal growth restriction, need to ventilatory support, neonatal infections. The information collected was compiled and their data entered in Epi Info version 6.04. Statistical analysis was performed using BioStat 5.0 program. For data analysis were applied to the chisquare test, G test and ANOVA and adopted the significance level α = 0.05. Results: When the variables related to low birth weight, prematurity (p <0.0001) and asymmetric fetal growth restriction (p <0.00001), there was an association of risk. The normal weight and Apgar score < 7 in the first minute had statistical correlation with p <0.00001. The severe hypertension had significantly increased risk for asymmetric fetal growth restriction (p <0.00001), Apgar score below 7 in the first minute (p <0.0004), need for ventilatory support (p <0.0071), neonatal infections with p <0.0164 and the presence of asymmetric fetal growth restriction (p <0.0007). Conclusions: The complication with the highest incidence was low birth weight represents, then the asymmetric fetal growth restriction infants and preterm delivery. The maternal and fetal prognosis is directly related to the severity of gestational hypertension / preeclampsia. Hypertension represents a serious risk factor for asymmetric fetal growth restriction, Apgar score below 7 in the first minutes of life, need for ventilatory support, infection and the occurrence of asymmetric fetal growth restriction infants. Complications that were associated with low birth weight births were premature and asymmetric fetal growth restriction infants, while the Apgar score at 1 minute less than 7 had a direct relationship with the normal birth weight.